Synthesis of oxazoles by silver catalysed oxidative decarboxylation–cyclization of α-oxocarboxylates and isocyanides1. Issue 52 (4th July 2015) - Ma, Yiyang; Yan, Zhiyuan; Bian, Changliang; Li, Ke; Zhang, Xiaowen; Wang, Mengfan; Gao, Xinlong; Zhang, Heng; Lei, Aiwen
<x xml:space="preserve">Abstract</x> This work developed a silver catalysed synthesis of oxazoles by the oxidative decarboxylation–cyclization of α-oxocarboxylates and isocyanides.